Clinical and Economic Burden of Managing Patients with Sickle Cell Disease Receiving Frequent Red Blood Cell Transfusions in the United States - Udeze C; Jerry M; Evans KA; Li N; Jain S; Andemariam B (ClinicoEconomics and Outcomes Research)
Chuka Udeze,1 Michelle Jerry,2 Kristin A Evans,2 Nanxin Li,1 Siddharth Jain,1 Biree Andemariam3 1Health Economics and Outcomes Research, Vertex Pharmaceuticals Incorporated, Boston, MA, USA; 2Research and Analytic Services, Merative, Ann Arbor, MI, USA; 3Medicine, University of Connecticut Health, Farmington, CT, USACorrespondence: Chuka Udeze, Health Economics and Outcomes Research, Vertex Pharmaceuticals Incorporated, 50 Northern Avenue, Boston, MA, 02210, USA, Email Chuka_udeze@vrtx.comPurpose: Standard of care for patients with sickle cell disease (SCD) includes red blood cell transfusions (RBCTs). Data on clinical and economic outcomes of patients with SCD receiving frequent RBCTs are limited.Materials and Methods: This longitudinal, retrospective, claims-based analysis used the Merative™ MarketScan® Commercial, Medicare, and Multi-State Medicaid databases. Patients with SCD (identified using ICD-9/10 codes) receiving frequent RBCTs (≥ 6 RBCTs during any 12-month period) between January 1, 2015, and March 1, 2019, were included. The index date was the date of the sixth RBCT. Eligible patients were required to have ≥ 12 months of continuous enrollment pre- and post-index. Patients were followed from index to end of enrollment, death, or end of the study period (February 29, 2020), whichever came first. Clinical complications, all-cause healthcare resource utilization (HCRU), and healthcare costs were descriptively summarized during follow-up.Results: A total of 919 patients with SCD receiving frequent RBCTs met the eligibility criteria for inclusion. Patients experienced a mean of 4.0 vaso-occlusive crises (VOCs) per patient per year (PPPY) and received a mean of 8.3 RBCTs PPPY during follow-up. The most common clinical complications were iron overload (77%), infections (66%), and cerebrovascular disease (48%). Patients had a mean of 2.3 inpatient admissions, 83.5 outpatient visits, and 37.4 outpatient prescriptions PPPY during follow-up. Mean total annual healthcare costs were $106,123 PPPY, including mean inpatient, outpatient medical, and outpatient pharmacy costs of $48,463, $28,307, and $29,353, respectively. Compared to those with < 2 baseline VOCs, patients with ≥ 2 baseline VOCs had more HCRU and higher annual healthcare costs.Conclusion: Despite utilizing available care with frequent RBCTs, patients with SCD experienced a variety of disease and transfusion-related complications, including frequent VOCs and iron overload, which led to substantial HCRU and costs. These findings highlight the need for novel therapies for this patient group.Keywords: complication, cost, healthcare resource utilization, vaso-occlusive crises, treatment